Coronavirus disease 2019 in dermatology practice: Perspective of three levels of prevention on public health - Chengwen Luo; Cai-Zheng Geng; Yung-Hsien Tung; Bing-Long Wang; Tao-Hsin Tung (Wolters Kluwer Medknow Publications, 2022)
Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2, has become a major public exigency of international concern. The COVID-19 epidemic has spread rapidly around the world, profoundly impacting people's lives. Patients are among those most affected by the pandemic. COVID-19 has adversely affected health-care systems, and the effects are long-lasting and devastating. Most medical institutions in the impacted countries and regions have been imbued with COVID-19 cases, both confirmed and suspected, leading to an overburdened health-care workforce like never before. While most of the critical situations involved internal medicine departments, such as infectious diseases, and intensive care units, other specialties, including dermatology, have also been profoundly affected by this pandemic. Dermatoepidemiology, the application of epidemiological methods to dermatology practice, is an important emerging discipline in dermatology. In this review, we discussed the influence of the COVID-19 epidemic on dermatology practice, as well as the application of public health strategies in dermatology. These findings from genetic epidemiological research, clinical trial networks, and pharmacovigilance research suggested that further research in dermatology requires collaborative studies across different fields, institutions, and countries. To solve the highly complex unsolved problems that we face, dermatologists and epidemiologists should be dynamic team members with multiple approach skills.